PENGARUH BUDAYA ORGANISASI DAN IKLIM KOMUNIKASI ORGANISASI TERHADAP LOYALITAS PENGURUS - Auliya Khairina Nurri, Ayub Ilfandy Imran (Universitas Informatika dan Bisnis Indonesia, 2018)
Young On Top Bandung is a community that focuses on developing the potential of young generation in skill, knowledge, and attitude. The purpose of this study was to determine the influence of organizational culture and organizational communication climate on organizer loyalty at Young On Top Bandung community. This study uses quantitative associative research. Sampling technique used was jenuh sampling type under non-probability sampling, with the total number of 67 respondents. The data was analyzed descriptively, and the hypothesis were tested by using multiple linear regression analysis. Based on the results of simultaneous hypothesis testing, organizational culture and organizational communication climate significantly influence organizer loyalty at Young On Top Bandung community. Based on the coefficient of determination, obtained value is 72,2%. The results showed that the effect of Organizational Culture and Organizational Communication Climate on Organizer Loyalty simultaneously gave the effect of 72,2% and the remaining 27,8% was influenced by other factors beside Organizational Culture and Climate Organizational Communication. Keyword: Organizational Culture, Organizational Communication Climate, Organizer Loyalty